FEATURES OF THE ENVIRONMENTAL SITUATION REGARDING WATER RESOURCES IN THE VOLODYMYR REGION OF VOLYN OBLAST - Мисковець, Ірина; Андрощук, Ігор (SWorldJournal, 2024)
The geological-geomorphological, climatic, and soil-vegetation conditions for the formation of water resources, including both surface and groundwater, in the Volodymyr region have been studied. The main factors influencing the geoecological status of su